Study of Alcohol Extract of Sesame on Wound Healing of Diabetic Male Wistar Rats - Mitra Bagheri; Sahar Molzemi; Mahbobeh Hadizadeh; Mohsen Aminian (Majallah-i Dānishkadah-i ̒ulūm-i Pizishkī-i Niyshābūr, 2016)
Introduction and Aims Diabetes is a metabolic disorder, which is characterized by hyperglycemia resulting from defects in insulin secretion and impaired pancreatic function. Regarding to the medicinal properties of amaranth, this study was conducted to investigate the effects of amaranth on skin histomorphological changes in diabetic rats. Materials and Methods In this study, 48 male Wistar rats were divided into four groups (control group, sham group, first experimental group, and second experimental group). In these rats, an injured area of 3cm2 was created on the left spine. Wound healing was evaluated macroscopically. Results Wound healing in group that became diabetes using streptozocin, showed late recovery compared to normal wound healing in normal groups and wound healing in experimental groups treated with alcohol extract of sesame was accelerated compared to control group. Conclusion Results of this study showed that alcohol extract of sesame causes accelerated skin wound healing in normal and diabetic samples.